(untitled) - Baldani, Jeffrey (Orlando, Florida, 1996)
The book presents a mathematical technique and its applications, extensive use of graphs, a review of basic differential calculuss, a good balance of micro- and macrieconomic models
Keywords: Economics, Mathematical